2014
DOI: 10.1186/s12977-014-0114-8
|View full text |Cite
|
Sign up to set email alerts
|

Re-visiting the functional Relevance of the highly conserved Serine 40 Residue within HIV-1 p6Gag

Abstract: BackgroundHIV-1 formation is driven by the viral structural polyprotein Gag, which assembles at the plasma membrane into a hexagonal lattice. The C-terminal p6Gag domain harbors short peptide motifs, called late domains, which recruit the cellular endosomal sorting complex required for transport and promote HIV-1 abscission from the plasma membrane. Similar to late domain containing proteins of other viruses, HIV-1 p6 is phosphorylated at multiple residues, including a highly conserved serine at position 40. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Consistent with our previous studies, it has been shown by others that the efficiency of virus release was not affected by mutation of Ser-40 [ 29 , 30 , 31 , 32 ]. In contrast, the E0A mutant, which also increased Gag membrane binding, displayed a severe budding defect.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our previous studies, it has been shown by others that the efficiency of virus release was not affected by mutation of Ser-40 [ 29 , 30 , 31 , 32 ]. In contrast, the E0A mutant, which also increased Gag membrane binding, displayed a severe budding defect.…”
Section: Discussionsupporting
confidence: 93%
“…Containing 5 positive and 9 negative charges, p6 displays an unusually high charge density, which might also be controlled by phosphorylation. It has already been described that phosphorylation of p6 at position 40 by aPKC [ 36 ] and at residue Thr-23 by Erk-2 [ 35 ] plays a role in virus release and infectivity, although its biological function is still under debate [ 25 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two substitutions that occurred at the same residue, S40F and S40A, were further investigated by engineering the individual substitutions into an HIV genome (pNL4-3). The substitution of F (S40F), where TCC = S to TTC = F, does not alter the sequence of the overlapping pol frame (TTC = F in the WT to TTT = F) but had an impact on several aspects of gag function [ 21 25 ]. The alanine (A) substitution (S40A), where TCC = S to GCC = A, in contrast, had a less deleterious effect on Gag processing, polyubiquitination or particle maturation morphology but altered the sequence at the p6*/PR cleavage site in the overlapping pol frame.…”
Section: Introductionmentioning
confidence: 99%
“…In a further step, mass spectrometry indicated the phosphorylation of S488 residue [85,86]. Its substitution with a hydrophobic aromatic residue such as phenylalanine (F), which can occur sponta-neously during anti-retroviral treatments, was found to perturb CA-SP1 processing, virus morphogenesis, maturation and virion infectivity [87][88][89]. On the other hand, the substitution of S488 by another non phosphorylable residue, such as asparagine (N), displayed no global impact on infectivity, thus suggesting that the production of non-mature viral particles would not be due to the lack of phosphorylation, but by the substitution itself [89].…”
Section: Hiv-1 Pr55 Gag Phosphorylationmentioning
confidence: 99%